Green Synthesis of Silver Nanoparticles from Morning Glory Leaf Extract (Ipomoea tricolor) and its Antibacterial Activity Against Pathogenic Bacteria - Eka Cahya Muliawati; Riri Oktaviani; Rahma Nurdi (CV. Get Press Indonesia, 2026)
Silver nanoparticles (AgNPs) have attracted considerable attention due to their exceptional physicochemical properties and broad-spectrum antibacterial activity. This study reports the first application of Ipomoea tricolor (morning glory) leaf extract distinguished by its uniquely high alkaloid (ergine, isoergine) and flavonoid (quercetin, rutin, kaempferol) content as a bifunctional bioreductant and capping agent for eco-friendly AgNP synthesis. Compared to commonly used plant sources, I. tricolor provides a rare combination of electron-rich phytochemicals that yield exceptionally small (18.4 ± 3.2 nm), highly stable (zeta potential: −32.4 mV, PDI: 0.214), and potently antibacterial nanoparticles without requiring additional stabilizers. Comprehensive characterization via UV-Vis (SPR at 425 nm), FTIR, XRD (FCC structure, 16.7 nm crystallite), TEM, and DLS confirmed nanoparticle formation and phytochemical capping. Antibacterial evaluation against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Streptococcus mutans demonstrated inhibition zones of 9.6–22.3 mm and MIC values of 6.25–25 µg/mL superior to AgNPs from most previously reported plant sources. These results establish I. tricolor-mediated AgNPs as promising sustainable candidates for biomedical applications, particularly in addressing antimicrobial resistance.